Improved Draft Genome Sequence of Bacillus sp. Strain YF23, Which Has Plant Growth-Promoting Activity - Xia, Ye (Microbiol Resour Announc, 2019)
We report here the improved draft genome sequence of Bacillus sp. strain YF23, a bacterium originally isolated from switchgrass (Panicum virgatum) plants and shown to exhibit plant growth-promoting activity. The genome comprised 5.82 Mbp, containing 5,933 genes, with 193 as RNA genes, and a GC content of 35.10%.